2013
DOI: 10.5463/dcid.v24i2.216
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Training of Children with Learning Disability

Abstract: Purpose: The ability to recognise emotions in oneself and in others is a fundamental prerequisite to function successfully in the social world. Emotion recognition deficit in people with learning disability may therefore be an important contributory factor to deficits in social skills and poor social adaptation. This study aimed to examine the level of emotional understanding in students with learning disabilities (LD). Method: A pre-test, post-test equivalent groups design was adopted for this study. The focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…They are perceived as less independent and have difficulties in waiting in turns, in learning in groups, and in making decisions during class activities [10]. However, one study determined that children with LD do not have significant effects on social or antisocial behaviors [6], and another that their sample with LD has better SEC than the rest of the boys and girls with different Special Education Needs (SEN) [8].…”
Section: Analysis Of Results On the Relationship Between Ld And Sec (Table 2)mentioning
confidence: 99%
See 4 more Smart Citations
“…They are perceived as less independent and have difficulties in waiting in turns, in learning in groups, and in making decisions during class activities [10]. However, one study determined that children with LD do not have significant effects on social or antisocial behaviors [6], and another that their sample with LD has better SEC than the rest of the boys and girls with different Special Education Needs (SEN) [8].…”
Section: Analysis Of Results On the Relationship Between Ld And Sec (Table 2)mentioning
confidence: 99%
“…The comparison of results between female and male sex is not one of the topics of greatest interest in this review. In those that do analyze it, it can be observed that the percentage of the sample of children and adolescents is higher than that of women [2,4,5,6,9]. Likewise, it is recognized that girls and adolescents obtain better scores in competences and social skills, while men have greater problems concerning antisocial behavior [6,7,9].…”
Section: Analysis Of Results On the Relationship Between Ld And Sec (Table 2)mentioning
confidence: 99%
See 3 more Smart Citations